Relationship between the concepts of renewable energies and environmental awareness of physics students - et. al., Ali Saad Abbas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to verify the level of acquisition by students of the physics department of the concepts of renewable energies and their level of environmental awareness, as well as to verify the type and degree of correlation between the students of the physics department’s acquisition of concepts of renewable energies and their environmental awareness, the researcher used the descriptive research method for its relevance to the nature of the research, and the formation of the research community of all the students of the physics departments in the faculties of education in the Iraqi universities in Baghdad governorate (Baghdad, Al-Mustansiriya and Al-Iraqia), the fourth stage of the morning study is (383) male and female, (152) male and female students from the University of Baghdad - College of Education for Pure Sciences Ibn Al-Haytham and from Al-Mustansiriya University (170) male and female students, and from the Iraqi University (61) male and female students, the research sample consisted of 304 male and female students from the research community, and the research tools consisted of testing the acquisition of the concepts of renewable energies that consisted of (54) item measuring elements of the concept at the level of definition, example and application, and the measure of environmental awareness that consisted of 65 item, the results showed that the students of the three physics departments acquired the concepts of renewable energies at the intermediate level, and that the students of the physics department at the University of Baghdad, Faculty of Education for Pure Sciences, Ibn al-Haytham, had a good environmental awareness, the students of the physics departments in the College of Education Al-Mustansiriya University and the Iraqi University have medium environmental awareness, and the results showed that there is a significant correlation between the acquisition of concepts of renewable energies and environmental awareness among the students of the research sample, and in light of the results, the researcher made a number of recommendations, including the need to pay attention to including education Environmental and renewable energies concepts in the curricula of the faculties of education, especially the Department of Physics, they also suggested conducting other studies similar to this study to complement the research.